A fibrin sealant for perforated and preperforated corneal ulcers. Issue 9 (September 1989) - Lagoutte, F M; Gauthier, L; Comte, P R
Abstract : Fibrin sealant is used to close perforated or preperforated corneal ulcers. In addition to the usual advantages of cyanoacrylates it is degraded physiologically and provides a good support for corneal healing. Corneal grafting can be avoided when contraindicated or postponed when conditions allow. This technique has been successful in nine eyes of eight patients.